Competitive ELISA for N-terminal pro-brain natriuretic peptide (NT-proBNP) determination in human plasma. Issue 20 (20th August 2020) - Colom, Glòria; Salvador, J.-Pablo; Acosta, Gerardo; Albericio, Fernando; Royo, Miriam; Marco, M.-Pilar
Abstract : A competitive ELISA has been developed for the determination of NT-proBNP using a rational hapten design for its antibody production and also, for the development of the ELISA. Abstract : Brain natriuretic peptides (BNPs) are well-established cardiovascular disease (CVD) biomarkers that are released from the heart after ventricular wall stress. Particularly, the N-terminal proBNP (NT-proBNP) is a 76 aa long peptide and is recognized as an indicator for the diagnosis of heart failure (HF) and is being used in routine tests in emergency rooms when levels are above 0.4 ng mL −1 . Herein, we report a new competitive ELISA for NT-proBNP, which is able to detect this biomarker directly in undiluted human plasma samples. The ELISA has been the result of a rational design of an immunizing peptide hapten and the investigation of different immunochemical conditions, including heterologous competitors and distinct physico-chemical conditions. The developed ELISA is able to detect NT-proBNP with a LOD of 0.40 ± 0.15 ng mL −1 in human plasma samples and quantify this biomarker in the range between 0.97 ± 0.38 and 23.10 ± 9.46 ng mL −1 with good accuracy. The ELISA can simultaneously measure many samples in 1.5 h and has been found to be robust, reproducible and shows great promise in diagnosis of heart failures.